Colloidal quantum dot solar cells - Emin, Saim; Singh, Surya P.; Han, Liyuan; Satoh, Norifusa; Islam, Ashraful (Solar energy, 2011)
In recent years colloidal quantum dots solar cells have been the subject of extensive research. A promising alternative to existing silicon solar cells, quantum dot solar cells are among the candidates for next generation photovoltaic devices. Colloidal quantum dots are attractive in photovoltaics research due to their solution processability which is useful for their integration into various solar cells. Here, we review the recent progresses in various quantum dot solar cells which are prepared from colloidal quantum dots. We discuss the preparation methods, working concepts, advantages and disadvantages of different device architectures. Major topics discussed in this review include integration of colloidal quantum dots in: Schottky solar cells, depleted heterojunction solar cells, extremely thin absorber solar cells, hybrid organic–inorganic solar cells, bulk heterojunction solar cells and quantum dot sensitized solar cells. The review is organized according to the working principle and the architecture of photovoltaic devices.